(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
Many fields of life has been used a robot, the specialty of the robot is coming from its accuracy. Therefore, this paper has been presented the evaluation of the robots arm performance on the one hand of consuming time and required end-position. Where, The time consuming required for the hand to reach to the desired position is taken 1.4614x10-4sec., while for finger adding to the arm is taken 0.00019sec.. Also, the error position has been evaluated with different NSPR (0.1-1) ,where the error amount are 0-12mm.